Peran Keluarga dalam Wirausaha Anak Muda - Anwar SA (Journal Economic Excellence Ibnu Sina, 2024)
This study aims to explore the role of families in supporting young entrepreneurs, which is often a determining factor in the success or failure of their business. Families can provide various forms of support, such as financial, emotional, knowledge, skills, and access to social networks that can accelerate business development. Using a qualitative research approach, data was collected through in-depth interviews with 8 young entrepreneurs in various business sectors in Sumbawa. The results of the study show that family support, both in the form of initial capital, knowledge guidance, and emotional motivation, has a significant role in increasing the confidence and resilience of young entrepreneurs. Nonetheless, some young entrepreneurs face challenges in convincing families who have a conservative view of entrepreneurship. This study indicates that the family is not only a provider of resources, but also as a psychological factor that can affect the success of young people's businesses. Therefore, the role of the family in young people's entrepreneurship needs to be strengthened through increased understanding and better support from the family.